Impaired autonomic function in normotensive obese children - Latchman, Peter L; Mathur, Madhu; Bartels, Matthew N; Axtell, Robert S; Meersman, Ronald E De (Clinical Autonomic Research, 2011)
Purpose To evaluate baroreflex sensitivity and autonomic control in a cohort of normotensive obese (OB) children. Method A cross-sectional investigation, in which, baroreflex sensitivity and autonomic control were evaluated using transfer function and power spectral density analysis (PSDA) of the electrocardiogram and beat-to-beat blood pressures in normotensive OB children and normal weight normotensive controls. All methods used were noninvasive and data were captured while seated and at rest. Results The OB and control subjects non-obese (NO) were of similar age (OB 9.1 ± 1.9 years vs.NO9.2 ± 1.4 years). The OB group was classified as having a BMI greater than the 95th percentile adjusted for age and gender, and a NO group with a BMI at or less than the 95th percentile (BMI percentile OB. 97.5 ± 1.3 vs. NO 58.5 ± 24.1). Both groups had similar normotensive blood pressures. T tests revealed that baroreflex sensitivity and HFRR were significantly reduced in the OB 9.2 ± 2.7 vs. 15.2 ± 4.7 (ms/mmHg) and 6.7 ± 1.1 vs. 8.2 ± 1.1 ms 2, respectively, while LF SBP and LF/HF ratio were significantly increased in the OB 11.9 ± 5.6 vs. 8.2 ± 4.7 mmHg 2 and 1.2 ± 0.7 vs. 0.54 ± 0.3, respectively. Conclusions Normotensive OB children exhibited significantly reduced baroreflex sensitivity, parasympathetic control as well as increased sympathetic control when compared with healthy, NO controls. Findings in this investigation raise the awareness that autonomic dysfunction is present in young OB normotensive children. © Springer-Verlag 2011.
29 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-898-861-083-084 tex.type: [object Object]
Keywords: Autonomic Nervous System; Autonomic modulation; Baroreflex sensitivity; Blood Pressure; Child; Cross-Sectional Studies; Female; Humans; Male; Normotensive; Obese children; Obesity; article; autonomic dysfunction; blood pressure; blood pressure measurement; body mass; body weight; child; clinical article; controlled study; dept.hms; electrocardiogram; female; human; male; obesity; pressoreceptor reflex; school child; sensitivity analysis

Spontaneous baroreflex sensitivity in young normotensive African-American women - Latchman, Peter; Gates, Gregory J; Axtell, Robert S; Pereira, Jason; Bartels, Matthew N; Meersman, Ronald Edmond De (Clinical Autonomic Research, 2013)
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/109-712-863-816-776 tex.type: [object Object]
Keywords: African American; European American; adult; article; body mass; breathing rate; clinical article; controlled study; dept.hms; diastolic blood pressure; family history; female; human; hypertension; physical activity; pressoreceptor reflex; race difference; systolic blood pressure